A Critical Investigation of the Wood Frame System: The Case for the Neil Astle House. Issue 1 (2nd January 2021) - Wrightsman, Bruce
Abstract : The traditional wood framed house has been a mainstay of the building industry and a dominant force on the American cultural landscape. With rare exceptions, its enormous effectiveness has seldom led to a serious questioning and challenging of what it means 'to build'. The act of building should be a reflective act, one that recognizes repercussions and limitations. One architect whose methodology challenged the residential construction paradigms and questioned how we build is Nebraska architect Neil Astle, who reenvisioned an alternative to traditional wood frame construction in the design of his house using small wood scantling.